The Effect of Internal Control, Marketing Strategy, and Product Innovation on Financial Performance of Food and Beverage UMKM - Hariyanto, Eko; Pramudya, Jidan (AMCA Journal of Community Development, 2026)
This study aims to analyze in depth the influence of internal control, marketing strategy, and product innovation on the financial performance of food and beverage UMKM in Purbalingga Regency. This study provides deeper insight into the factors that influence the financial performance of UMKM, as well as providing practical recommendations for UMKM actors to improve their performance. This study uses a quantitative approach with an associative method to analyze the relationship between internal control, marketing strategy, and product innovation on the financial performance of food and beverage UMKM in Purbalingga Regency. Data were collected using a questionnaire. The analysis technique applied is Structural Equation Modeling (SEM) using SmartPls software. The results of the analysis show that Internal Control is acceptable, which means that the factor has a significant effect on the financial performance of MSMEs. On the other hand, marketing strategy has a positive role but does not have a significant effect, and product innovation does not show a positive and insignificant role. Therefore, MSMEs are advised to stabilize internal control, improve digital marketing strategies, and develop product innovation. Further research is needed to explore other factors that affect the financial performance of MSMEs.